Pengembangan Daya tarik dan Strategi Pemasaran Tempat Wisata Melalui Kegiatan Branding Wana Sumber Biru - Fidda Rahmawati; Indah Respati Kusumasari (Jurnal Akuntan Publik, 2023)
Tourism is a creative economy-based service industry that is very important for the progress of the Unitary State of the Republic of Indonesia. Tourism in Indonesia has great potential and makes a significant contribution to the economy, job creation, infrastructure development and community empowerment, including in rural areas. With good and sustainable management, tourism can grow in a sustainable manner and provide long-term benefits. Selection of tourist attractions can be adjusted to the goals of each tourist. The tourist village is a tourist attraction that can be developed and can make a positive contribution to the people of Jombang. The tourist spot chosen in this research is Sumber Biru tourism area. The implementation method used in this study is a qualitative approach with types of observation, documentation, and literature studies to obtain information about the problems faced by blue tourism sources starting from tourism development such as repairing or updating photo spots and obstacles in tourism promotion. The population in this activity were managers and visitors to the Sumber Biru tourism area which had been analyzed by KKNT students. In this community service, the team hopes to contribute more to Wonomerto village so that it can have a positive impact on local residents, especially on Sumber Biru tourism.